COVID-19 and Acute Otitis Media in Children: A Case Series. (March 2022) - Frost, Holly M.; Sebastian, Thresia; Keith, Amy; Kurtz, Melanie; Dominguez, Samuel R.; Parker, Sarah K.; Jenkins, Timothy C.
Background: The association of SARS-CoV-2 with acute otitis media (AOM) in children is poorly understood. Methods: Cases were identified as a subpopulation within the NO TEARS prospective AOM study in Denver, CO from March to December 2020. Children enrolled were 6 to 35 months of age with uncomplicated AOM; those with AOM and SARS-CoV-2 were included. Data was obtained from electronic medical records and research case report forms. Results: A total of 108 patients enrolled in the NO TEARS study from May 2019 through December 2020 (all subsequently tested for SARS CoV-2). During the COVID-19 pandemic study period (March-December 2020), 16 patients enrolled, and 7 (43.6%) were identified with AOM/COVID-19 co-infection. Fever was present in 3 of 7 children (29%). Four children (57%) attended daycare. Only 2 children (29%) had SARS CoV-2 testing as part of their clinical workup. Mean AOM-SOS © scores were similar among SARS CoV-2 positive and negative patients with no statistical significance with two-sided t -tests: 13.6 (±4.5) versus 14.2 (±4.9) at enrollment, 1.4 (±1.8) versus 4.2 (±4.9) on Day 5, and 0.6 (±0.9) versus 2.5 (±6.1) on Day 14. Among the 7 cases, no child had an AOM treatment failure or recurrence within 3 to 14 or 15 to 30 days respectively. Of the 6 patients with completed bacterial and viral testing, a bacterial pathogen was identified in all 6, and a viral pathogen in 3 (50%). Conclusions: COVID-19 and AOM can co-exist. Providers should maintain a high index of suspicion for COVID-19 even in patients with clinical AOM and should not use a diagnosis of AOM to exclude COVID-19.